2005
DOI: 10.1532/ijh97.04129
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Variant of T-Cell Prolymphocytic Leukemia with a 33 Immunophenotype

Abstract: T-cell prolymphocytic leukemia (T-PLL) is a rare postthymic T-cell disorder. The disease is characterized by lymphadenopathy, splenomegaly, skin lesions, a high white blood cell count, and an aggressive clinical course. The small cell variant of T-PLL occurs in approximately 20% of patients. Most T-PLL patients express membrane T-cell receptors (TCR) of the alphabeta phenotype. The diagnosis of small cell variant T-PLL in a 56-year-old woman was based on the findings of abnormal lymphocytosis, immunophenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…The frequency of 14q32 abnormalities on conventional cytogenetic analysis ranged from 25 to 76.6% in cases with T-PLL [1][2][3]. A total of 30 T-PLL cases, including 11 in the present study, have been reported in Japan [21,[26][27][28][29][30][31][32][33][34]; however, the frequency of typical chromosomal abnormalities involving 14q32 and Xq28 is low (3.3%) according to conventional methods. These data confirm a previous report [21].…”
Section: Discussionmentioning
confidence: 82%
“…The frequency of 14q32 abnormalities on conventional cytogenetic analysis ranged from 25 to 76.6% in cases with T-PLL [1][2][3]. A total of 30 T-PLL cases, including 11 in the present study, have been reported in Japan [21,[26][27][28][29][30][31][32][33][34]; however, the frequency of typical chromosomal abnormalities involving 14q32 and Xq28 is low (3.3%) according to conventional methods. These data confirm a previous report [21].…”
Section: Discussionmentioning
confidence: 82%
“…However, because of the aggressive clinical course that defines most cases of T-PLL, it was reclassified by the World Health Organization (WHO). [1][2][3][4][5][6] Among the classic clinical features are lymphocytosis, lymphadenopathy, cutaneous disease, and splenomegaly. 3,5,6 One of the characteristic features of T-PLL is cutaneous involvement; the reported incidence is between 25% and 30%.…”
Section: T -Cell Prolymphocytic Leukemia (T-pll) Is a Distinctive Formentioning
confidence: 99%
“…Clonal rearrangement of T cell receptors is present in all cases of T-PLL with TCRαβ phenotypes being the most common. TCRγδ phenotypes have been reported in rare instances [11,12]. …”
Section: Review Of Literaturementioning
confidence: 99%